ANALISIS WILLINGNESS TO PAY (WTP) MASYARAKAT TERHADAP RETRIBUSI PENGELOLAAN SAMPAH DI GAMPONG PEUNAGA BARO KABUPATEN ACEH BARAT - saputri, lisa indah; Badli, Saiful; Juliansyah, rollis; Suhendra, Noval; Alisman, Alisman (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2023)
This study aims to analyze the factors influencing the willingness to pay (WTP) for waste management fees among the community in Gampong Peunaga Baro, West Aceh Regency. The variables examined include education level, income, occupation, and frequency of waste collection. This research employs a quantitative approach using a survey method, and data analysis is conducted through multiple linear regression to determine the effect of each variable on WTP. The population consists of all household heads in Gampong Peunaga Baro, with purposive sampling applied to select 297 respondents who are considered knowledgeable and relevant to the waste management issue. The results indicate that education and income have a positive and significant influence on the community’s ability to pay waste fees, while occupation and frequency of waste collection do not have a significant effect. These findings highlight the importance of considering socioeconomic factors when designing waste fee policies to enhance community participation and improve the sustainability of waste management.